Assessing the toxicity of sediments using the medaka embryo–larval assay and 2 other bioassays. (15th June 2016) - Barhoumi, Badreddine; Clérandeau, Christelle; Landi, Laure; Pichon, Anaïk; Le Bihanic, Florane; Poirier, Dominique; Anschutz, Pierre; Budzinski, Hélène; Driss, Mohamed Ridha; Cachot, Jérôme
Abstract: Sediments are sinks for aquatic pollutants, and analyzing toxicity in such complex matrices is still challenging. To evaluate the toxicity of bioavailable pollutants accumulated in sediments from the Bizerte lagoon (Tunisia), a novel assay, the medaka embryo–larval assay by sediment contact, was applied. Japanese medaka ( Oryzias latipes ) embryos were incubated in direct contact with sediment samples up to hatching. Lethal and sublethal adverse effects were recorded in embryos and larvae up to 20 d postfertilization. Results from medaka embryo–larval assay were compared with cytotoxicity (Microtox®), genotoxicity (SOS chromotest), and pollutant content of sediments. The results highlight differences in the contamination profile and toxicity pattern between the different studied sediments. A significant correlation was shown between medaka embryo–larval assay by sediment contact and SOS chromotest responses and concentrations of most organic pollutants studied. No correlation was shown between pollutant levels and Microtox. According to the number of sediment samples detected as toxic, medaka embryo–larval assay by sediment contact was more sensitive than Microtox, which in turn was more sensitive than the SOS chromotest; and medaka embryo–larval assay by sediment contact allowed sediment toxicity assessment of moderately polluted sediments without pollutant extraction and using an ecologically realistic exposure scenario. Although medaka embryo–larval assay by sediment contact should be tested on a larger sample set, the results show that it is sensitive and convenient enough to monitor the toxicity of natural sediments. Environ Toxicol Chem 2016;35:2270–2280. © 2016 SETAC